PENGARUH PROFESIONALISME, KOMITMEN ORGANISASI, DAN LOCUS OF CONTROL TERHADAP INTENSI AUDITOR UNTUK MELAKUKAN TINDAKAN WHISTLEBLOWING PADA KANTOR PUBLIK DI KOTA MAKASSAR - Hs, Sri Wahyuni (IJMA (Indonesian Journal of Management and Accounting), 2024)
This study aims to determine the Effect of Professionalism, Organizational Commitment and Locus of Control on the Auditor's Intention to Perform Whistleblowing Actions. The data of this research is primary data, by distributing questionnaires to 35 auditors who work in Public Accounting Firms in Makassar City. The survey was conducted from June to July 2021. The analysis technique used in this study was multiple linear regression analysis. The results of this study indicate that Professionalism has a positive effect on the Auditor's Intention to Whistleblowing, Organizational Commitment has a positive and significant effect on the Auditor's Intention to Whistleblowing, and Locus of Control has a positive and significant effect on the Auditor's Intention to Whistleblowing.